SELEMBAYUNG - Indah Ratna Sari (Saraswati)
Selembayung in  other  word  is  sulobayung and  tandukbuang which  has  meaning adornment that cross locating at both of roof ofmelayuRiau house. Selembayung contains a symbol which has a meaningful, that is why the relief is  as power of the house that can shine up the building till the sharp-end of the roof. Selembayung relief gives an inspiration to the maker to invent great work of art by themes are meaningful and philosophy point that in selembayung which is aplicating from the corak balam dua setengger application. The selection of melayu Riau culture  andSiak especially as an orientation in dance project, because the background of the artists are from Siak. The work of art is expected can give some advantages to Siak society.  Key Words: Koreografi, Selembayung, Garis